Buschke-Löwenstein Tumor: report of three cases - Gazelli, Mayra Cavalcante; Jorge, Iago Farias; Santiag, Muse de Oliveira; Rebouças, Karinne Cisne Fernandes; Cavalcante, Diane Isabelle Magno; Coelho, Raquel Autran (Brazilian Journal of Sexually Transmitted Diseases, 2017)
The Buschke-Löwenstein Tumor is a rare, sexually transmitted disease, triggered by human papillomavirus, specially the subtypes 6 and 11. It is characterized as a cauliflower-shape exophytic mass, slowly progressive, with high local recurrence rates and high infiltration. The main risk factor is immunosuppression. Surgical treatment is usually preferred, with or without adjuvant therapy. It has a great impact on the patients’ life, impairing their life quality. We report three cases of Giant Condyloma with diverse histopathological findings with varying degrees of infiltration and papillomatosis.